Web Search Results Personalization - Salim, Sayed Suhel Mohd. (IJRDO -Journal of Computer Science Engineering, 2015)
In the present scenario information can be achieved easily through web. Although search engines provide plenty of data but it has a drawback that the information is not correct. According to research users lack interest if it is time consuming and does not provide accurate data. So search engines must provide accurate data. Since personalized web environments provide exact and instant data both to short term and long term users there is an increase in its demand. We have given various personalization techniques and approaches in this paper.